2004
DOI: 10.1211/0022357045048
|View full text |Cite
|
Sign up to set email alerts
|

Natural phenylpropanoids inhibit lipoprotein-induced endothelin-1 secretion by endothelial cells

Abstract: There is increasing evidence that oxidized low-density lipoproteins (Ox-LDL) might be involved in the pathogenesis of atherosclerosis and it has been reported that polyphenols inhibit LDL peroxidation and atherosclerosis. Endothelin-1 (ET-1) is a potent vasoconstrictor peptide isolated from endothelial cells and it induces smooth muscle cell proliferation. ET-1 secretion is increased in atheroma and induces deleterious effects such as vasospasm and atherosclerosis. The goal of this study was to test the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This protective effect can be mainly attributed to the free radical scavenging property of the PhGs. Furthermore, the inhibition of copper-oxidized LDL-induced endothelin-1 liberation by acteoside, forsythoside B, arenarioside, and ballotetroside (95) indicates that these PhGs may be potential therapeutic tools for controlling atherosclerosis [71]. In another study by He et al, acteoside, 2'-acetylacteoside, poliumoside, and brandioside from…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%
“…This protective effect can be mainly attributed to the free radical scavenging property of the PhGs. Furthermore, the inhibition of copper-oxidized LDL-induced endothelin-1 liberation by acteoside, forsythoside B, arenarioside, and ballotetroside (95) indicates that these PhGs may be potential therapeutic tools for controlling atherosclerosis [71]. In another study by He et al, acteoside, 2'-acetylacteoside, poliumoside, and brandioside from…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%
“…In human endothelial cells in culture, PPAR α ligands inhibit the cytokine/LPS induction of COX-2 [38, 69], ICAM-1 [91], VCAM-1 [29, 31], endothelin-1 [92], IL-6, and prostaglandin E 2 [32, 93]. Similarly, PPAR α ligands repress thrombin-induced expression of endothelin-1 [32].…”
Section: Pparα and Pparγ: Anticancer Targets In The Endotheliummentioning
confidence: 99%
“…A study by Jiang et al (16) showed that forsythiaside reduced serum levels of TNF-α and IL-6, decreased the infiltration of leukocytes and reduced the histopathological damage in a rat myocardial ischemia-reperfusion (I/R) model. In addition, Forsythiaside has been demonstrated to attenuate lipid peroxidation, decrease lipoprotein-induced endothelin-1 secretion by endothelial cells and inhibit COX-2 activity (1719). However, the effect of forsythiaside on the inflammatory cytokine production induced by LPS in broiler chickens has not been investigated.…”
Section: Introductionmentioning
confidence: 99%